The Influence of Motivational Dynamics and Work Discipline on Superior Performance: Case Study at PT Pegadaian Ciputat Branch - Kusuma, Alan Budi; Amalia, Rizky; Riesmiyantiningtias, Ninuk; Abdurrachman, Abdurrachman (ProBisnis : Jurnal Manajemen, 2023)
This research aims to investigate the influence of motivation on employee performance, the impact of work discipline on employee performance, and the combined influence of motivation and work discipline on employee performance at PT Penggadaian Branch Ciputat. The research employs a quantitative approach with observation, questionnaires, and documentation as the outlined methods for the thesis. The study involved 40 employees at PT Penggadaian Branch Ciputat. The findings reveal that there is a positive and significant influence of motivation on employee performance, there is a positive and significant impact of work discipline on employee performance, there is a positive and significant combined influence of motivation and work discipline on employee performance. The conclusion has important implications for HR management in the company. Management can focus on improving employee motivation and discipline to support overall performance improvement. However, this research has limitations, especially in terms of generalizing the results, as it was conducted only at PT. Pegadaian Branch Ciputat and involved a sample of 40 employees. Therefore, further research can be expanded to other branches and involve more respondents to obtain a more comprehensive overview.